Prediction of Reverberant Properties of Enclosures via a Method Employing a Modal Representation of the Room Impulse Response - MEISSNER, Mirosław (Archives of Acoustics, 2016)
A theoretical method has been presented to describe sound decay in building enclosures and to simulate the room impulse response (RIR) employed for prediction of the indoor reverberation characteristics. The method was based on a solution of wave equation having the form of a series whose time-decaying components represent responses of acoustic modes to an impulse sound source. For small sound absorption on room walls this solution was found by means of the method of variation of parameters. A decay function was computed via the time-reverse integration of the squared RIR. Computer simulations carried out for a rectangular enclosure have proved that the RIR function reproduces the structure of a sound field in the initial stage of sound decay suffciently well. They have also shown that band-limitedness of the RIR has evident influence on the shape of the decay function and predicted decay times.